Soil moisture droughts in East Africa: Spatiotemporal patterns and climate drivers - Yongwei Liu; Yuanbo Liu; Wen Wang; Xingwang Fan; Wei Cui (Journal of Hydrology: Regional Studies, 2022)
Study region: East Africa (EA). Study focus: The current poor capability of drought resistance and the high dependence of local residents on agriculture and animal husbandry initiated a comprehensive understanding of soil moisture (SM) droughts in EA. Previous lower-order subspace drought investigations that have neglected the space–time continuity of actual droughts hindered deeper knowledge of droughts. To fill this gap, this study investigated the SM droughts in EA from a space–time joint perspective, focusing on drought spatiotemporal patterns and variations, and climate drivers. New hydrological insights for the region: Based on the space–time joint approach, 582 drought clusters and 226 events over 1979–2014 were identified. Spatially, historical droughts presented a dual-centre pattern in the northwest and southeast; they were characterised by high frequency, long duration, and large severity, driven by the climate forcing of precipitation (Prep) and temperature (Temp). This pattern differed seasonally due to the major control of Prep and the partly strengthening effect of Temp. Temporally, seasonal droughts displayed significant (p < 0.05) increasing/decreasing trends in summer/autumn. Regarding the climate drivers, the partial least squares regression approach was first employed in the space–time continuous drought domain. The innovative method clarified the contribution of different climate elements to SM droughts and recognised the critical climate drivers of Prep, wind speed, and downward radiation. The results provides important implications for drought mechanism exploration and drought prediction.